Family Caregivers' Lived Experiences for Post-Stroke Patients: A Qualitative Study - Rosina Tarigan; Setyowaty; Rr. Tutik Sri Hariyati; Salim Harris; Debie Dahlia; Muchtaruddin Mansyur (Talenta Publisher, 2024)
Stroke survivors in Indonesia depend on their families to meet their daily needs. Therefore, the function of family caregivers in stroke patients is essential in helping to meet their needs. This study aims to determine family caregivers' lived experiences for post-stroke patients. The study design was a qualitative descriptive phenomenology with a sample of 6 participants recruited by purposive sampling. Instruments include semi-structured questions, field notes, and a voice recorder. Data was analysed using the thematic content analysis method. This study was conducted from October 2021 to February 2022 at the Gisting Health Center, Tanggamus Regency, Lampung Province, Indonesia. The study found three main themes and seven sub-themes. The themes were knowledge of stroke (sub-themes: stroke disease and stroke management), seeking treatment (sub-themes: following community habits, drug therapy according to what is felt useful, alternative therapies produced by factories), and Difficulty in taking care (sub-themes: difficulties caring for patients at home and efforts to solve the difficulties). In conclusion, caregivers have Difficulty taking care of post-stroke patients at home and in the community. Nurses can participate as nurses in community health centres and family health nurses in providing comprehensive care and educating caregivers on how to take care of post-stroke patients properly.